DISTRIBUTION, STRUCTURE AND PRODUCTIVITY OF OAK STANDS IN WEST UKRAINE - Kopiy, Leonid; Kopiy, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2024)
Oak forests in the study region cover an area of 461.5 thousand ha, which amounts to nearly 27.1% of Ukraine’s oak forests. The age structure of the stands analyzed, is essentially disturbed. A major portion is made up of middle-aged stands (over 57.2%), somewhat less is represented by stands of sapling stage (21.1%), and the smallest part is made up of mature stands (6.3%). It has been found that in the most representative forest type (moist hornbeam oakery) in the western part of the study region, a substantial proportion of the area is occupied by secondary stands. For oak stands of fertile site type forests in the study region, a clear-cut relationship is shown between the increase in the area of secondary stands and periods of improperly conducted silvicultural measures of oak trees tending.